Divergent impact of progesterone and medroxyprogesterone acetate (Provera) on nuclear mitogen-activated protein kinase signaling - Nilsen, Jon (National Academy of Sciences, 2003)
The impact of progestins on estrogen-inducible mechanisms of neuroprotection was investigated. Previously, we showed that estrogen and progesterone are neuroprotective against excitotoxicity, whereas the synthetic progestin medroxyprogesterone acetate (MPA; Provera) is not. Here, we demonstrate that 17β-estradiol (E(2)) and progesterone (P(4)) treatment of hippocampal neurons attenuated the excitotoxic glutamate-induced rise in intracellular calcium concentration. Although MPA had no effect alone, MPA completely antagonized E(2)-induced attenuation of intracellular calcium concentration. Activation of extracellular receptor kinase (ERK) is required for estrogen-induced neuroprotection and calcium regulation. Paradoxically, E(2), P(4), and MPA all elicited similar rapid and transient activation of ERK, presenting a contradiction between the dependence on ERK for gonadal hormone-induced neuroprotection and the lack of neuroprotection induced by MPA. Subcellular analysis of ERK demonstrated that the phospho-ERK signal is transduced to the nucleus only by E(2) and P(4), not by MPA. These results indicate that the profile of nuclear translocation of ERK is consistent with the neuroprotective profile. Further, the E(2)-induced nuclear translocation of ERK was blocked by coadministration of MPA. Results of this study reveal that nuclear ERK induction by ovarian steroids is predictive of the neuroprotective effects of estrogen and progestin treatments, revealing a hitherto unrecognized divergence of progestin signaling through the src/MAPK pathway. These results have much broader implications encompassing the impact of progestins on estrogen-mediated effects in multiple tissues. The recent results from the Women's Health Initiative trial, which used MPA as the progestinal agent, indicate that differences between progestin formulations are crucial to health outcomes in women.